2018
DOI: 10.3126/jcmsn.v14i1.18761
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Regarding Prevention of Mother to Child Transmission of HIV/AIDS among Antenatal Mothers in Nepal

Abstract: Background & Objectives:Prevention of Mother to child Transmission (PMTCT) is a global intervention which aims at preventing mother to child transmission of Human Immunodeficiency Virus (HIV). The study aims to find out knowledge of pregnant women on Mother to child Transmission (MTCT) of HIV/AIDS (Acquired Immune Deficiency Syndrome).Materials & Methods:A cross-sectional study was carried out at Paropakar Maternity and Women’s Hospital, Kathmandu, Nepal among the pregnant women who came to visit Anten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 6 publications
(8 reference statements)
6
7
0
Order By: Relevance
“…Similar to our study, these two studies also found that none of the women mentioned health professionals as a source of information of HIV and AIDS (Pandey, 2013;Acharya et al, 2017). The major sources of information of HIV and AIDS in these studies were Radio, Television, and Newspapers (Pandey, 2013;Acharya et al, 2017). Similar to our study, the majority of women in both studies said that HIV and AIDS is transmitted from unprotected sexual contact (Pandey, 2013;Acharya et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar to our study, these two studies also found that none of the women mentioned health professionals as a source of information of HIV and AIDS (Pandey, 2013;Acharya et al, 2017). The major sources of information of HIV and AIDS in these studies were Radio, Television, and Newspapers (Pandey, 2013;Acharya et al, 2017). Similar to our study, the majority of women in both studies said that HIV and AIDS is transmitted from unprotected sexual contact (Pandey, 2013;Acharya et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…So, it is crucial to start health education on HIV and AIDS at the ANC clinic to provide basic knowledge about HIV and AIDS that encourages pregnant women for laboratory tests related to this infection as well as prevention and management of HIV/AIDS While some of our study findings are similar with other studies, some of our study findings are different or show lower percentage of pregnant women who have knowledge of HIV and AIDS than in other studies conducted in Nepal (Pandey, 2013;Acharya et al, 2017). Similar to our study, these two studies also found that none of the women mentioned health professionals as a source of information of HIV and AIDS (Pandey, 2013;Acharya et al, 2017). The major sources of information of HIV and AIDS in these studies were Radio, Television, and Newspapers (Pandey, 2013;Acharya et al, 2017).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The majority of pregnant women (72.7%) had a high level of PMTCT knowledge. This was consistent with a hospital-based cross-sectional survey carried out in Kathmandu (Nepal), where 84.4% of pregnant women knew all three MTCT transmission routes, although knowledge of drugs to prevent it was relatively low [23]. However, the level of PMTCT knowledge found in our study was higher than in two Ethiopian institutional-based surveys in Assosa town (57.5%) [24] and East Gojjam (52%) [25], and 48% at Kiisi referral hospital in Kenya [26].…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, the majority of pregnant women (83.4%) had a high HIV prevention knowledge. This result was also in line with a Nepali findings [23]. Furthermore, 85.5% of pregnant women knew that limiting sexual life to a single not infected with HIV partner and condom use with occasional partners, can reduce the risk of HIV infection, as compared to 68% found in IMASIDA, 2015 [8] and 63.8% observed at community-based cross-sectional survey in Northeast Ethiopia in Meket [18].…”
Section: Discussionsupporting
confidence: 85%